2017
DOI: 10.1080/17470218.2016.1178785
|View full text |Cite
|
Sign up to set email alerts
|

Executive Function and Intelligence in the Resolution of Temporary Syntactic Ambiguity: An Individual Differences Investigation

Abstract: In the current study, we examined the role of intelligence and executive functions in the resolution of temporary syntactic ambiguity using an individual differences approach. Data were collected from 174 adolescents and adults who completed a battery of cognitive tests as well as a sentence comprehension task. The critical items for the comprehension task consisted of object/subject garden paths (e.g., While Anna dressed the baby that was small and cute played in the crib), and participants answered a compreh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
55
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 132 publications
(206 reference statements)
6
55
4
Order By: Relevance
“…Though some have argued that such a lack of correlated variation reflects domain-specificity (Acheson & Hagoort, 2014; Engelhardt et al, 2016; Vuong & Martin, 2014), we have been arguing that this null pattern does not necessarily indicate support for domain-specificity, particularly in view of our co-localization patterns (see also Miyake & Friedman, 2004; Unsworth, 2010). Rather, a lack of correlated variation in LIFG activity may simply index distinct task demands, differences in information content, and variability in how much conflict each task elicits relative to baseline.…”
Section: Resultsmentioning
confidence: 61%
See 3 more Smart Citations
“…Though some have argued that such a lack of correlated variation reflects domain-specificity (Acheson & Hagoort, 2014; Engelhardt et al, 2016; Vuong & Martin, 2014), we have been arguing that this null pattern does not necessarily indicate support for domain-specificity, particularly in view of our co-localization patterns (see also Miyake & Friedman, 2004; Unsworth, 2010). Rather, a lack of correlated variation in LIFG activity may simply index distinct task demands, differences in information content, and variability in how much conflict each task elicits relative to baseline.…”
Section: Resultsmentioning
confidence: 61%
“…Though a range of prior neuroimaging, behavioral, and patient data suggest that common cognitive control procedures help language users resolve conflict during sentence comprehension (Hsu & Novick, 2016; Humphreys & Gennari, 2014; January et al, 2009; Novick et al, 2005, 2009; van de Meerendonk et al, 2013; Vuong & Martin, 2011; Ye & Zhou, 2009), other data suggest distinctions in the cognitive control systems that operate over syntactic and non-syntactic material, leading to claims of domain-specificity (Acheson & Hagoort, 2014; Engelhardt et al, 2016; Fedorenko et al, 2012; Vuong & Martin, 2014). Our study tested the effects of increased conflict resolution demands across four diverse tasks, one of which involved syntactic conflict and three of which did not.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lexically-encoded information comprises phonological, semantic, or syntactic information, as well as implicit information about the frequency of that word being followed by another word. Previous studies on cognitive processing have been conducted to better understand how the parser accesses and uses that lexical information during online comprehension (e.g., Altmann et al 1998;Anisimov et al 2014;Coco and Keller 2015;Demestre and García-Albea 2004;Dussias 2003;Dussias and Scaltz 2008;Dussias and Sagarra 2007;Engelhardt et al 2017;Fernández 2003;Garnsey et al 1997;Havik et al 2009). These studies have suggested that, with enough experience with a language, the linguistic system can extract lexically-encoded information, including the probability of a specific word to be followed by a preferred continuation over several competing possibilities, to anticipate upcoming linguistic information in a sentence (e.g., Altmann 1998).…”
Section: Introductionmentioning
confidence: 99%